Physical and neural entrainment to rhythm: human sensorimotor coordination across tasks and effector systems - Ross, Jessica Marie; Balasubramaniam, Ramesh (Frontiers in Human Neuroscience, 2014)
The human sensorimotor system can be readily entrained to environmental rhythms, through multiple sensory modalities. In this review, we provide an overview of theories of timekeeping that make this neuroentrainment possible. First, we present recent evidence that contests the assumptions made in classic timekeeper models. The role of state estimation, sensory feedback and movement parameters on the organization of sensorimotor timing are discussed in the context of recent experiments that examined simultaneous timing and force control. This discussion is extended to the study of coordinated multi-effector movements and how they may be entrained.